Performance improvement of electric vehicle inductive-power transfer system using series-series capacitor compensation - Sabki S.A.; Tan N.M.L. (Institute of Electrical and Electronics Engineers Inc., 2023)
Capacitors; Electric power systems; Electric vehicles; Energy conversion; Energy dissipation; Low power electronics; Reconfigurable hardware; Vehicles; Capacitor compensation; Compensation capacitors; Inductive power transfer; Inductive power transfer systems; Inductive powertransfer (IPT); Secondary circuit; Series capacitor compensation; Wireless power transfer; Inductive power transmission